2019
DOI: 10.1186/s12933-019-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of diabetes mellitus treated with oral antidiabetic drugs and insulin with mortality after transcatheter valve implantation: a 3-year follow-up of the TAVIK registry

Abstract: Background Diabetes mellitus (DM) on insulin is a patient-related factor in the assessment of surgical risk based on the EuroSCORE II and, as such, it confers additional risk on outcomes after transcatheter aortic valve implantation (TAVI). The aim of this study was to investigate the effect of diabetes mellitus treated with insulin and oral antidiabetic drugs on clinical outcomes after TAVI. Methods This study is an analysis of 2000 patients who underwent TAVI between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…p < 0.05) after TAVI. However, insulin-treated diabetes was not identified as an independent risk factor for higher mortality in the 1st (HR 1.29; 95% CI 0.97-1.72, p = 0.084) and 3rd years (HR 1.21; 95% CI 0.98-1.49; p = 0.079) after multivariable adjustment [116]. Similarly, DM was not associated with a higher 30-day or 12-month allcause mortality after TAVI, nor was it associated with decreased post-procedural QoL [117].…”
Section: Sglt2 Inhibitors and Cardiovascular Outcomesmentioning
confidence: 88%
“…p < 0.05) after TAVI. However, insulin-treated diabetes was not identified as an independent risk factor for higher mortality in the 1st (HR 1.29; 95% CI 0.97-1.72, p = 0.084) and 3rd years (HR 1.21; 95% CI 0.98-1.49; p = 0.079) after multivariable adjustment [116]. Similarly, DM was not associated with a higher 30-day or 12-month allcause mortality after TAVI, nor was it associated with decreased post-procedural QoL [117].…”
Section: Sglt2 Inhibitors and Cardiovascular Outcomesmentioning
confidence: 88%
“…These findings question whether 1‐year is sufficient period to evaluate impact of DM on clinical outcome in patients with TAVR. Most recent multicenter registry, 10 which analyzed data of 3‐year follow up, suggested that DM group had significantly higher mortality. However, previous studies which evaluated diabetic effects on 1‐ or 2‐year mortality have reported mixed results 5,6,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a well‐established marker of poor prognosis in various cardiovascular diseases 3,4 . However, controversy remains regarding impact of DM on clinical outcomes after TAVR 5–12 . Various factors may exist for the different results among previous reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM is an established component of pre-operative risk assessment in AS patients and was an independent predictor of mortality also in our research. Although diabetic patients presented an overall lower survival than those without diabetes, insulin-treated diabetes was not an independent risk factor for higher mortality in a recent analysis [ 28 ]. Among female patients of the WIN-TAVI international registry, DM was not associated with increased mortality after TAVR [ 29 ].…”
Section: Discussionmentioning
confidence: 99%